Plain talk : lessons from a business maverick - Iverson, Ken (Wiley, 1998)
Ken Iverson, the Chairman of Nucor Corporation, says many things you wouldn't expect to hear from a Fortune 500 executive. But then, few top executives are such fervent champions of the front-line worker. Now, in his long-awaited book, this visionary maverick shares valuable lessons about what it takes to build a super-competitive, world-class business. Nucor - a $3.8 billion dynamo of profitable growth - disdains committees, job descriptions, performance appraisals, and everything else bearing the taint of bureaucracy. Iverson believes people should earn according to what they produce. And he relentlessly "destroys hierarchy" to eliminate the trappings that distance managers from employees. Nucor has never laid off an employee or shut down a facility for lack of work. Instead, the company has followed Iverson's controversial "painsharing" approach. When times get tight, everyone takes paycuts - starting with the executives at the top.